2005
DOI: 10.1007/s00170-004-2435-6
|View full text |Cite
|
Sign up to set email alerts
|

A study of the Taguchi optimization method for surface roughness in finish milling of mold surfaces

Abstract: The objective of this paper is to develop a Taguchi optimization method for low surface roughness in terms of process parameters when milling the mold surfaces of 7075-T6 aluminum material. Considering the process parameters of feed, cutting speed, axial-radial depth of cut, and machining tolerance, a series of milling experiments were performed to measure the roughness data. A regression analysis was applied to determine the fitness of data used in the Taguchi optimization method using milling experiments bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 10 publications
0
37
0
1
Order By: Relevance
“…If some parameters do not significantly affect the CTQ, they can be ignored and excluded from predictive model generation and the optimization process. This will increase the efficiency of the optimization process [10]. Therefore, ANOVA is repeated again ignoring all the non-significant factors, refer Table 4: ANOVA on significant effects…”
Section: Analysis Of Variance (Anova)mentioning
confidence: 99%
“…If some parameters do not significantly affect the CTQ, they can be ignored and excluded from predictive model generation and the optimization process. This will increase the efficiency of the optimization process [10]. Therefore, ANOVA is repeated again ignoring all the non-significant factors, refer Table 4: ANOVA on significant effects…”
Section: Analysis Of Variance (Anova)mentioning
confidence: 99%
“…Anastasiou [9] investigated the effects of process parameters on porosity formation in the pressure die casting process to improve casting quality using Taguchi method. Oktem et al [10], developed a Taguchi optimization method for low surface roughness for milling an aluminum alloy. Kittur et al [11] demonstrated the effect of die casting machine parameters (fast shot velocity, slow shot to fast shot change over point, intensification pressure and holding time) on the performance characteristics of die casting process using response surface methodology (RSM).…”
Section: Introductionmentioning
confidence: 99%
“…Öktem et al [11] have studied the surface roughness of mould obtained by treating the Aluminium alloy end cutter with AlTiN-coated solid carbide. Milling experiments were carried out in the mould cavity of a 7075-T6 Aluminium block with dimensions of 120 × 120 × 50 mm.…”
Section: Introductionmentioning
confidence: 99%